2011
DOI: 10.1007/s00438-011-0608-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics of Lactobacillus sakei with emphasis on strains from meat

Abstract: Lactobacillus sakei is a lactic acid bacterium important in food microbiology mainly due to its ability to ferment and preserve meat. The genome sequence of L. sakei strain 23K has revealed specialized metabolic capacities that reflect the bacterium's adaption to meat products, and that differentiate it from other LAB. An extensive genomic diversity analysis was conducted to elucidate the core features of the species, and to provide a better comprehension of niche adaptation of the organism. Here, we describe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 94 publications
1
55
0
Order By: Relevance
“…For example, the conversion of arginine, an alternative energy source abundantly present in meat due to endogenous protease activity, through the ADI pathway renders this species with an improved survival in the stationary growth phase (4,5,31,43). Arginine conversion is a common metabolic trait for the species L. sakei and is encoded by the arc operon (24,41,42). In L. sakei CTC 494, the arc operon (arcABCTDR) shows the same gene order and organization as that of L. sakei 23K (42).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the conversion of arginine, an alternative energy source abundantly present in meat due to endogenous protease activity, through the ADI pathway renders this species with an improved survival in the stationary growth phase (4,5,31,43). Arginine conversion is a common metabolic trait for the species L. sakei and is encoded by the arc operon (24,41,42). In L. sakei CTC 494, the arc operon (arcABCTDR) shows the same gene order and organization as that of L. sakei 23K (42).…”
Section: Discussionmentioning
confidence: 99%
“…Fresh meat contains a relatively restricted amount and diversity of carbohydrates, consisting mostly of glucose at levels of between 0.2% and 1.0% (16,20). To effectively cope with this environment, a flexible use of all available energy sources and nutrients present in meat is of importance (20,24). In this sense, an efficient catabolism of nucleosides by L. sakei provides this species with an additional energy source (31).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The second-generation LAB starter cultures, now widely used, are often based on these [69]. Molecular characterization by, for example, genome sequencing and comparative genomics has shown that strains of L. sakei isolated from meat and meat fermentation have evolved to be perfectly adapted to this particular environment [70][71][72]. L. plantarum lacks this specific adaptation but is a fast-growing, highly flexible bacterium with the largest genome size of the lactobacilli.…”
Section: Starter Culturesmentioning
confidence: 99%
“…The only lactobacillus with a characterized lactose PTS is Lactobacillus zeae (Alpert & Chassy, 1990;Chassy et al, 1976;Chassy & Thompson, 1983;Gosalbes et al, 1999). However, lactose-specific PTS genes have recently been indentified using bioinformatics in Lactobacillus sakei (Nyquist et al, 2011) and Lactobacillus iners (Macklaim et al, 2011), suggesting that lactose-specific PTSs are not rare amongst lactobacilli.…”
Section: Introductionmentioning
confidence: 99%